Programa educativo de netiqueta en directivos y docentes para mejorar la convivencia social online en la Institución Educativa Primaria N° 61015 la Inmaculada Punchana 2021 - Del Aguila Trigoso, Ana (2023)
In Punchana district, this research was developed to respond to the hypothesis the application of the netiquette educational program in managers and teachers significantly improves online social coexistence in the Primary Educational Institution No. 61015, and for this reason to evaluate the effect of the application of the mentioned program. The type of evaluative research was considered, as well as the longitudinal, field, and quasi-experimental design with a single group. The study population consisted of 47 teachers and managers, who were also the sample, in which an entrance and exit test was applied through a written performance test, an instrument that was validated by experts. Its conclusion is that the effect of the application of the netiquette educational program to managers and teachers to improve online social coexistence of the Primary Educational Institution No. 61015, is effective because it is observed that before the application of the program 2.1 % (n=1) was located at the beginning level in online social coexistence, 63.8% (n=38) at the process level and 34.1% (n=16) at the expected achievement level, no manager and teacher showed outstanding achievement. After the application of the program, 6.4% (n=3) are observed at the process level, 85.1% (n=40) at the expected level of achievement and 8.5% (n=4) at outstanding achievement level.